Nano-sandwiched metal hexacyanoferrate/graphene hybrid thin films for in-plane asymmetric micro-supercapacitors with ultrahigh energy density. Issue 5 (20th February 2019) - He, Yafei; Zhang, Panpan; Wang, Mao; Wang, Faxing; Tan, Deming; Li, Yang; Zhuang, Xiaodong; Zhang, Fan; Feng, Xinliang
Abstract : In-plane asymmetric micro-supercapacitors with ultrahigh energy density are rationally constructed using nano-sandwiched metal hexacyanoferrate/graphene hybrid thin films. Abstract : In-plane micro-supercapacitors (MSCs) with high power density, remarkable rate capability, and long cycling stability, exhibit promising application potential in modern electronic devices. To satisfy the fast-growing energy demands for the next-generation advanced micro-devices, increasing the energy density of MSCs is urgently desirable but still remains a great challenge. In this work, a series of in-plane asymmetric MSCs (AMSCs) are rationally constructed using a family of nano-sandwiched metal hexacyanoferrate/graphene hybrid thin films with interdigital patterns. The voltage output window of the resultant AMSCs is able to reach up to 1.8 V, delivering superior areal capacitances of up to 19.84 mF cm −2, and ultrahigh energy density of 44.6 mW h cm −3 which is among the best performances of the state-of-the-art MSCs. Moreover, the achieved AMSCs show outstanding mechanical flexibility and integration capability. Thus, this work will promote the development of novel high-performance AMSCs.